A Comprehensive Overview of Respiratory Compliance in Dogs Under General Anesthesia: Clinical Factors and Future Perspectives - Tingfeng Xu; Ahmed S. Mandour; Kazumi Shimada; Lina Hamabe; Ryou Tanaka (Animals)
Respiratory compliance reflects the ability of the lungs and chest wall to expand in response to increases in pressure. In this review, relevant studies were selected through a comprehensive literature search with the aim of summarizing and generalizing them to describe the relevant factors that may be present in veterinary clinical practice and affect respiratory compliance in dogs. Individual factors, including breeds, disease background, drugs administered, and especially surgical procedures, can result in alterations to respiratory compliance due to their impact on the respiratory system in dogs. Despite its potential clinical utility, such as in anesthesia monitoring, respiratory compliance remains underutilized in veterinary medicine, and further research is necessary to support its future clinical applications.